MOLECULAR CHARACTERIZATION OF MBL IN UROPATHOGENIC E. COLI ISOLATED FROM PATIENTS OF TERTIARY CARE HOSPITAL - Sabahat Asghar; Abid Ali Khuwaj; Muhammad Arfat; Noreen Taj; Maria Akhtar; Ihsan Ullah (Journal of Ayub Medical College Abbottabad, 2024)
Background: Antibiotic resistance is on an increasing trend, particularly in gram-negative bacteria. The production of metallo Î²-lactamase (MBL) puts the health sector at great risk as it further limits the treatment option for MDR strain. MBL is mostly reported in Enterobacteriaceae, which poses resistance to almost all Î²-lactam antibiotics except monobactam. The current study aims to determine the prevalence, antibacterial sensitivity pattern, and molecular characterization of MBL in Uropathogenic E. coli from clinical samples of hospitalized patients in Khyber Pakhtunkhwa. Methods: From tertiary care hospitals in Peshawar, 250 Urine samples were collected from indoor hospitalized patients. Gold standard microbiological methods were used to identify UPEC from these clinical samples.For that,urine samples was inoculated onto Cysteine Lactose Electrolyte. Deficient (CLED) agar plate, and MacConkey Agar.Positive growth of E.coli identified through Gram staining, colony morphology, Biochemical Tests and E.coli 16srRNA gene amplification .Antibiotic sensitivity was determined by the disc diffusion method on Muller Hinton agar. For the detection of MBL production double disc synergy, and a combination disc test of the antibiotics were used. Furthermore, multiplex PCR was used for the molecular characterization of the MBL (blaIMP, blaVIM, and blaNDM) genes. Results: Of the 250 samples, only 110 samples were confirmed as Uropathogenic E. coli based on colonial morphology, biochemical testing, and molecular level by targeting the 16SrDNA. Female was found more susceptible to UTI compared to male. High prevalence was found in the age group 45-65 years. UPEC was found highly resistance to Ciprofloxacin (90%), followed by Cefotaxime and Ceftriaxone (86%), Ceftazidime and Augmentin (81%), Tazobactam (61%). while the lowest resistance was reported against Meropenum (20%) Imipenem (18%) and Amikacin (37%). PCR-based confirmed prevalence of MBL encoding genes was blaNDM (42%), blaVIM (32%), and blaIMP (26%). Conclusion: The study proposed a higher prevalence of urinary tract infections (UTIs) in females aged group 54-65 years compared to males. An analysis of antibiotic sensitivity revealed Imipenem and Meropenem to be the most effective antimicrobial agents, while Ciprofloxacin, Cefotaxime and Amoxicillin were found to be the less effective. UPEC were found highly resistance to Ciprofloxacin 91%, and ceftazidime 86%, while comparatively less resistance to meropenem, and imipenem,20% and 18% respectively. Genotype BlaNDM of the MBL is highly prevalent (42%) among UPEC.Furthermore, the presence of MBL genes was detected in over 19% of UPEC, and in different combinations.The upraise of the MBLs resistance in uropathogenic E. coli is an alarming sign for clinicians to decide on treatment options for complicated UTIs.